On two-color partitions - Robbins, Neville (Utilitas Mathematica, 2004)
Let q2(n), q2*(n) denote respectively the number of partitions of n in two colors into distinct parts, distinct odd parts. We derive recursive identities concerning q2(n) and q2*(n).